Sex-specific differences in placental global gene expression in pregnancies complicated by asthma - Osei-Kumah, A.; Smith, R.; Jurisica, I.; Caniggia, I.; Clifton, V.L. (Placenta (Eastbourne), 2011)
Chronic maternal asthma is associated with reduced growth of the female fetus and normal growth of the male fetus. The mechanisms that control the differential effects of maternal asthma on the fetus have not been fully elucidated but alterations in placental function may play a role. In the current study we have used microarray platform to examine fetal sex-specific global changes in placental gene expression in pregnancies complicated by asthma as compared to non-asthmatic subjects. Placental RNA was extracted from 11 control subjects and 38 asthmatic subjects. Labeled cDNA was hybridized to an oligonucleotide chip with 1700 double spotted well-characterized human genes. Global gene expression data analysis and visualization were performed using the Binary Tree-Structured Vector Quantization (BTSVQ) software. Functional relationships of differentially expressed genes were assessed using protein–protein interaction database I2D, network analysis and visualization software NAViGaTOR and Ingenuity Pathway Analysis software. Overall, 65 genes were found to be altered in placentae of pregnancies complicated by asthma. Of these, only 6 genes were altered in male placentae. There were 59 gene changes in female placentae of asthmatic mothers relative to control placentae. Some of the sex-specific genes were associated with growth, inflammation and immune pathways. There are sex-specific alterations in placental gene expression in the presence of maternal asthma. Given that many of the identified genes in the female placentae were associated with or involved in cellular growth and tissue development, these may contribute to the sexually dimorphic difference in fetal growth in response to maternal asthma.